The effect of straight-line and accelerated depreciation rules on risky investment decisions: An experimental study - Hagen Ackermann; Martin Fochmann; Nadja Wolf (International Journal of Financial Studies, 2016)
The aim of this study is to analyze how depreciation rules influence the decision behavior of investors. For this purpose, we conduct a laboratory experiment in which participants decide on the composition of an asset portfolio in different choice situations. Using an experimental setting with different payment periods, we show that accelerated compared to straight-line depreciation can increase the willingness to invest as hypothesized by theory. However, this expected behavior is only observed in a more complex environment (with a subsidy) and not in a less complex environment (without a subsidy).
Keywords: C91; D14; H24; 330; taxation; behavioral accounting; behavioral taxation; straight-line depreciation; accelerated depreciation; tax perception; risk-taking behavior; portfolio choice